Influences of Urea and Za Fertilizers to Soil Chemical Properties, N Uptake and Sugarcane Growth in Ultisols Seputih Mataram, Lampung - Wan Tarmizi; Sri Nuryani Hidayah Utami; Eko Hanudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Ultisols is a less fertile soil also esay to soil leaching and erosion can cause lower efficiency of soil nutrient uptakes such as Nitrogen. The objective of this research was to find out the influences of Urea and ZA fertilizers to soil chemical properties, N uptake and sugarcane growth in Seputih Mataram Ultisols in Lampung. The experiment was conducted in a completely randomized design in 2 factors and 3 blocks for repetitions. The first factor was the sugarcane varieties; TC-09 (V1) sugarcane variety and TC-15 (V2) sugarcane variety. The second factor was fertilizer doses and combinations in 7 levels: 0 kg N/ha or without N fertilizer (N0); 100% of urea fertilizer from total of standard dosage of SGC (151 kgs of N/ha), which is 328 kg Urea/ha (N1); 86% urea and 14% ZA or 283 kg urea/ha and 100 kg ZA/ha (N2); 75% urea and 25% ZA or 246 kg urea/ha and 100 kg ZA/ha (N3); 50% urea and 50% ZA or 164 kg ura/ha and 360 kg ZA/ha (N4); 25% urea and 75% ZA or 82 kg urea/ha and 539 kg ZA/ha (N5); and 100% ZA fertilizer of 719 kg ZA/ha (N6). This results showed that Urea at the dosage of 328 without Za is the most effective and economist combination to increase the weight of sugar-cane per hectare, N uptake of plants, and N efficiency uptake of plants. Additional dosage of ZA increased soil acidity (decreased of soil pH). The study also showed recent that the weight and amount of population per hectare of TC 15 variety are higher than TC 09 variety.